EVALUATION OF UMBILICAL CORD THICKNESS AND ITS ASSOCIATION WITH ANTENATAL MATERNAL RISK FACTORS - SWAROOP SINGH; PUNEET JAIN; SUNNY MALVIA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: The umbilical cord provides the pathway for unhindered blood transport from the placenta to the foetus and vice versa. Antenatal risks may lead to change in the thickness of umbilical cord thickness. The aim of the study was to determine the association between umbilical cord thickness and antenatal maternal risk factors. Methods: This was a cross sectional prospective study conducted between Jan 2023 to Dec 2023 at department of Pediatrics, Pacific Medical College and Hospital, Udaipur, India. Total 400 newborn subjected for this study. Out of these 200 newborn enrolled as control group for this study. Informed consent was obtained from the caregivers. Institutional ethical committee approval was sought before the start of the study. Results: Mean umbilical cord diameter among neonates with antenatal risk factors (UCD in mm) was11.53 ± 2.59 and mean umbilical cord diameter among newborns without antenatal risk factors was 12.23 ± 2.43 respectively. The difference in UCD in mm among cases and controls was significant (P < 0.05). Bad obstetric history and PIH was associated with significant change in umbilical cord thickness. Among cases, 23% neonates required NICU admission and 77% did not require NICU admission whereas among controls, only 0.5% neonate required NICU admission and 99.5% did not require NICU admission. There was significant association between NICU admission among cases and control group. (P<0.05) Conclusion: Presence of antenatal risk factors leads to significant change in umbilical cord thickness. Thin umbilical cord has been found to be associated with need of NICU admission.